Peningkatan Inovasi dan Penjualan UMKM SINOM SI MANIES CAK ENDUT melalui Strategi Pemasaran Digital: Peningkatan Inovasi dan Penjualan UMKM SINOM SI MANIES CAK ENDUT melalui Strategi Pemasaran Digital - Wildan Sam Aden; Erfin; Ahmad Rizal Tohari; Reza Ichsan Mashuda; Moh. Zakaria Zakki; Anita Firdaus; Moh. Mustofa; Adrian Wahyu Adi Saputra; Alfin Setya Ningrum; Ika Widya Ardhyani; Khoirul Ngibad (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
The selected KKNT-KWU UMAHA partner is the traditional drink business "Sinom Si Manies Cak Endut" which was founded five years ago and is located on Jl. Raya Semambung No. 409 Lopang Hamlet, Driyorejo District, Gresik Regency. The partner's problems include the following: sinom products are only marketed by word of mouth, and through social media, sinom production is only carried out according to consumer demand. This KKNT-KWU UMAHA activity aims to help overcome partner problems in marketing using social media "Instagram". KKNT-KWU UMAHA activities include observation and discussion with partners to analyze the problems experienced by partners, assistance to partners to start marketing products through social media "Instagram" and assistance to partners to make Instagram feeds to be more attractive and modern to attract the attention of social media users "Instagram". The KKNT-KWU UMAHA activities result in partners having excellent and attractive product photos. In addition, the KKNT-KWU UMAHA activities are able to improve the MSME management process so that there is an increase in turnover and quality of partner products.